A resolved RANS CFD approach for drag characterization of antifouling paints. (1st January 2019) - Niebles Atencio, Bercelay; Chernoray, Valery
Abstract: Prediction of mean flow and turbulence structure of boundary layer on surfaces with roughness is still not fully understood in fluid mechanics. Specific characteristics of roughness in terms of shape, size and distribution vary from case to case. Current paper shows a method for obtaining the roughness function of any arbitrary rough surface by using resolved RANS simulations in channel flows, which are considerably cheaper in terms of time and resources when compared with experiments and other modeling approaches (LES/DNS). Drag characterization and roughness function determination were studied for a particular antifouling paint with different roughness used in marine applications. Reynolds numbers based on channel height were in the range 84000-280000. Roughness functions from resolved RANS simulations were compared with those obtained for the same coating from two of the most commonly used experimental techniques: a rotating disc rig and towing tank. Data obtained from all three methods were successfully fitted on same roughness function curve. Furthermore, to check consistency between the obtained roughness function and drag prediction by using this function, CFD simulations of flat plate flow using standard wall functions were performed. Total drag of a plate from computational results deviated by around 7% with results from experiments. Highlights: Drag characterization of antifouling paints was carried out by means of resolved RANS CFD simulations. RANS CFD can be an inexpensive alternative to find the roughness function for any arbitrary roughness. Improved accuracy of CFD is required to better match experiments. Agreement is seen between the experimental approaches. The equivalent sand-grain roughness could also be easily determined.